Fresno County Bar Association's Annual Judges' Dinner at Bob Crossland's Barn - Watkins, Howard::::::::: (1982)
Musicians: Judge James V. Paige on drums, trombonist, Robert Oliver on trumpet, Truman Campbell on clarinet